Anticorpos dirigidos a antígenos próprios do hospedeiro e sua relação com a anemia em infecções por Plasmodium vivax - Gustavo Pereira Cardoso de Oliveira (2024)
One of the major complications of Plasmodium vivax infection is anemia. The parasite’s biological cycle involves the destruction of infected erythrocytes, but this alone would not justify the anemic condition presented by vivax malaria patients. This is because this species exclusively invades reticulocytes, which make up about 1% of circulating bood cells. Consequently, several studies have proposed that autoimmune mechanisms resulting from the infection could be correlated with the destruction of uninfected erythrocytes, leading to anemia. Some erythrocyte molecules have been identified as potential targets of autoantibodies generated by self-reactive cells, such as band 3 and phosphatidylserine. Thus, employing a serological approach, we evaluated antibody levels against erythrocyte own molecules, as well as autoantibodies directed towards nucleic acids and healthy, intact erythrocytes. Our data demonstrates that anemic patients (Hb < 12 g/dL) infected with P. vivax have significantly higher levels of antibodies against these molecules compared to patients without anemia. Additionally, these antibody levels correlate negatively with the hemoglobin and hematocrit levels of these individuals. Using Principal Component Analysis, we found that the presence of these antibodies is associated with infection but is not influenced by the specific anti-parasitic response (measured by the presence and levels of antibodies against one merozoite protein, the PvMSP-119), nor by parasitemia and previous exposure to malaria. To confirm the opsonization of these antibodies in healthy erythrocytes and evaluate their possible effect on blocking band 3 ion channels, we conducted flow cytometry assays in the presence or absence of H2DIDs. In the presence of this band 3 ion channel blocker, there was an increase in opsonization by antibodies from infected patients, with or without anemia. Furthermore, only anti-band 3 antibody levels correlated positively with the opsonization rate of uninfected erythrocytes. Accordingly, we conducted an Immunoblot assay using the complete amino acid sequence that comprises the band 3 protein to determine the most recognized portions of this protein by antibodies present in the plasma of anemic individuals. Thus, we selected two promising peptides corresponding to two distinct portions of the protein, one intracellular and the other related to the ion channel, which are significantly recognized by anemic patients infected with P. vivax. The generated data contribute to understanding the determinants of anemia in vivax malaria and enhance the knowledge of the epitope spreading of band 3 protein with the formation of neoantigens during P. vivax infection.